Information Retrieval and Search Engines in Full-text Databases - Zillmann, Hartmut (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2000)
OSIRIS and ELIB are two cooperative projects at the Osnabrück University supported by the German Research Society (DFG) and the Ministry of Science and Culture (MWK) Niedersachsen (Germany). They deal with natural language retrieval systems and with indexing techniques for full-text databases using natural language processing. Very complex processes in the context of syntactical and semantical analysis of textual phrases including sophisticated valuation criteria could be implemented in large relational databases with online realtime indexing requirements.